2008
DOI: 10.1371/journal.pgen.1000061
|View full text |Cite
|
Sign up to set email alerts
|

Primary Coenzyme Q Deficiency in Pdss2 Mutant Mice Causes Isolated Renal Disease

Abstract: Coenzyme Q (CoQ) is an essential electron carrier in the respiratory chain whose deficiency has been implicated in a wide variety of human mitochondrial disease manifestations. Its multi-step biosynthesis involves production of polyisoprenoid diphosphate in a reaction that requires the enzymes be encoded by PDSS1 and PDSS2. Homozygous mutations in either of these genes, in humans, lead to severe neuromuscular disease, with nephrotic syndrome seen in PDSS2 deficiency. We now show that a presumed autoimmune kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
147
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(164 citation statements)
references
References 35 publications
9
147
0
Order By: Relevance
“…The normal levels of renal CoQ 9 indicate that impaired CoQ biosynthesis is not a primary determinant of the kidney disease of MMA (Table S4) and is consistent with the distinct renal pathology exhibited by the Mut −/− ;Tg INS-Alb-Mut animals compared with a model of defective CoQ biosynthesis, the Pdss2 kd/kd mice (28). However, the decrease in renal CoQ 10 in the Mut −/− ;Tg INSAlb-Mut mouse kidney extracts paralleled a previous report of reduced CoQ 10 concentrations in MMA patient fibroblasts (29) and further suggested that markers of oxidant stress be explored in both animals and patients.…”
Section: Discussionsupporting
confidence: 60%
“…The normal levels of renal CoQ 9 indicate that impaired CoQ biosynthesis is not a primary determinant of the kidney disease of MMA (Table S4) and is consistent with the distinct renal pathology exhibited by the Mut −/− ;Tg INS-Alb-Mut animals compared with a model of defective CoQ biosynthesis, the Pdss2 kd/kd mice (28). However, the decrease in renal CoQ 10 in the Mut −/− ;Tg INSAlb-Mut mouse kidney extracts paralleled a previous report of reduced CoQ 10 concentrations in MMA patient fibroblasts (29) and further suggested that markers of oxidant stress be explored in both animals and patients.…”
Section: Discussionsupporting
confidence: 60%
“…Scale bars: 1 mm (D); 100 μm (E and F). of COQ6 mutations is remarkably similar to that of mutations in COQ2 (23) and PDSS2 in humans (34) and Pdss2 in mice (24), all of which respond to CoQ 10 treatment (12,35). Patients with defects in genes required for CoQ 10 biosynthesis - PDSS2, COQ2, and COQ9 - exhibit renal disease, and in some cases there is a dramatic response to CoQ 10 therapy, but this is quite variable (36).…”
Section: Coq6 Mutations Cause Srns With Sensorineural Deafness (Snd)mentioning
confidence: 67%
“…Interestingly, 1 patient with mutations in COQ2 was successfully treated with oral CoQ 10 supplementation, showing progressive recovery of renal function and a reduced level of proteinuria until 5 years after completion of treatment (22). The podocyte-specific phenotype caused by PDSS2 mutations leading to primary CoQ 10 deficiency was demonstrated in the Pdss2 knockout mouse (24). Conditional knockouts targeted to renal tubular epithelium, monocytes, or hepatocytes did not show disease manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in mouse models have established that loss of Pdss2 function in the podocyte is sufficient to recapitulate the kidney phenotype observed in individuals with genetic causes of primary coenzyme Q 10 deficiency. 57 While decrements in oxidative phosphorylation may contribute to podocyte damage and the nephrotic proteinuria observed with primary coenzyme Q 10 deficiencies, there may also be a role for the antioxidant function of coenzyme Q 10 or in de novo pyrimidine biosynthesis. 53 Interestingly, a recent report examined the role of PDSS2 in a cohort of individuals with focal segmental glomerulosclerosis.…”
mentioning
confidence: 99%